STATUS GIZI, ASUPAN CAIRAN DAN KEBUGARAN JASMANI ATLET DI PERSATUAN BULUTANGKIS KABUPATEN KUDUS - Fitri Rachma; Siti Zulaekah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Achievement of badminton athlete performance is supported by excellent physical fitness, normal nutritional status and adequate fluid intake. The purpose of this study was to determine the relationship of nutritional status and fluid intake with physical fitness athletes in Badminton Association of Kudus Regency. This research is an observational research with cross sectional approach. The populations in the study were badminton athletes in Kudus Region who met the inclusion criteria. Samples used 33 samples from the total population of 85 samples. Analysis of the relationship of nutritional status and fluid intake with athlete's physical fitness using Pearson Product Moment test. Based on the test of the relationship of nutritional status with athlete physical fitness obtained p value = 0.386. Analysis of the relationship of fluid intake with athlete's physical fitness obtained p value = 0.450. This study can be concluded that there is no relationship of nutritional status and fluid intake with athlete's physical fitness.